2013
DOI: 10.4172/2155-9600.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethephon and Ethylene Gas on Ripening and Quality of Tomato (Solanum Lycopersicum L.) during Cold Storage

Abstract: The investigation was carried out to obtain information about effect of ethephon and ethylene gas on ripening and quality of winter tomato (cv. Hybrid-1001). The mature green tomatoes were treated with different concentrations of aqueous solution of ethephon (500, 1000 and 1500 ppm) for 5 minutes, thereafter packed in plastic crates and kept in storage room at 20 ± 1°C and 90-95% RH. In another experiment, mature green tomatoes were exposed to ethylene gas (100 ppm) inside the ripening chamber for 24 hours (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
6
15
1
Order By: Relevance
“…It clearly indicated that ethephon was more effective in early ripening of tomatoes as compared to untreated. Higher concentration of ethephon increases the ripening time of fruits [4,9]. Improved ripening with post-harvest ethephon application is due to the binding of ethylene to the receptor, which forms an activated complex that leads to a wide variety of physiological responses, including ripening [20].…”
Section: Effect Of Ethephon On Ripening Time and Shelf Life Of Tomatomentioning
confidence: 99%
See 3 more Smart Citations
“…It clearly indicated that ethephon was more effective in early ripening of tomatoes as compared to untreated. Higher concentration of ethephon increases the ripening time of fruits [4,9]. Improved ripening with post-harvest ethephon application is due to the binding of ethylene to the receptor, which forms an activated complex that leads to a wide variety of physiological responses, including ripening [20].…”
Section: Effect Of Ethephon On Ripening Time and Shelf Life Of Tomatomentioning
confidence: 99%
“…Fruits and vegetables are generally rich sources of vitamins, minerals, phytochemicals, dietary fibers, carotenoids and polyphenols [1][2][3]. Tomato (Lycopersicon esculentum) is the most important fruit of the world including tropical, subtropical and temperate regions [4]. It is widely used by food industries as a raw material for the production of different products such as puree or ketchup.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among fruits and vegetables, tomato ranks 16 th and 13 th as a source of vitamin A and vitamin C respectively. Lycopene that imparts red color to ripe tomatoes is very important nutrient as it possesses anti-cancerous properties [2][3] reduce ovarian tumor growth [4] and prevent oral disease [5]. Tomato and its product can help to prevent CVD diseases [6][7] and provide an effective means against numerous type of cancers [8].…”
Section: Introductionmentioning
confidence: 99%